Preparation, physicochemical characterization, dissolution and formulation studies of telmisartan cyclodextrin inclusion complexes - Kane, Rajesh N; Kuchekar, Bhanudas S (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this research was to prepare, characterize, and to study dissolution properties of inclusion complexes of telmisartan (TLM), with Î²-cyclodextrin and hydroxypropyl-Î²-cyclodextrin and to study effect of complexation on aqueous solubility and rate of dissolution in dissolution media. The phase solubility curve was classified as an AP type for both the CDs, which indicated formation of the inclusion complex of TLM in 1:2 stoichiometries with Î²-CD and HP-Î²-CD. The inclusion complexes in molar ratio of 1:2 were prepared by various methods. The molecular behavior of TLM in all samples were characterized by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and powder X-ray diffraction studies.The result of studies showed inclusion of TLM molecule into cyclodextrin cavities.The highest improvement in in-vitro dissolution of TLM was observed in a complex prepared with HPÎ²-CD using the kneading method. Mean dissolution time (MDT) and similarity factor (f2) indicated a significant difference between the release profile of TLM from complexes, physical mixture, and pure TLM. The highest improvement in solubility and in-vitro drug release were observed in inclusion complex prepared with HP-Î²-CD by kneading method. Improvement in solubility and in-vitro drug release of telmisartan was more with HP-Î²-CD as compared to Î²-CD